DEVELOPING THE PEDAGOGICAL RESPONSIBILITY OF PRIMARY TEACHERS IN AN INCLUSIVE EDUCATION SETTING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the inclusive education system and its basic principles, especially the need and directions for developing the pedagogical responsibility of primary school teachers. The professional qualifications of teachers, emotional stability, their role in adapting the educational process, and pedagogical approaches are highlighted. Practical recommendations are also provided.